Self-doped porous carbon derived from acacia plantation residues for green-supercapacitor in sustainable energy applications - Apriwandi, Apriwandi; Deniza, Rindhu Nabila; Martin, Awaludin; Julnaidi, Julnaidi; Taslim, Rika; Taer, Erman (Faculty of Engineering Universitas Riau and Applied Materials and Technology Society, 2025)
To improve bio-organic-carbon quality for supercapacitors, consider using dual or more heteroatom for more profitable carbon-chain doping. Developing suitable sources and preparation strategies is challenging but essential. Herein, we introduce a potential carbon source derived from acacia plantation residues, doped with boron, oxygen, and phosphorus. The pore structure of this carbon material can be precisely tuned to exhibit a well-defined hierarchical arrangement of micro-, meso-, and macropores through a low-ratio of phosphoric acid (H?PO?) impregnation method combined with dual-environment (N2 and CO2) vertical pyrolysis in one step integrated. The resulting material displays a confirmed hierarchical morphology with a hierarchical transformation into tunnel pores, in specific surface area of 521.70 m²/g which contributed to high charge storage and deliverability. Additionally, the material contains significant levels of boron (0.93%), oxygen (9.19%), and phosphorus (0.34%), facilitating a reversible Faradic reaction in the working electrode. Consequently, optimized-electrode achieves a specific capacitance of 198 F/g at 1 A/g in H?SO? electrolyte. In a two-electrode system, records energy density of 14 Wh/kg (1 A/g) at a maximum power density of 670 W/kg (10 A/g). These findings suggest that the natural incorporation of boron, oxygen, and phosphorus enhances both the activity and the hierarchical pore structure of carbon derived from acacia plantation residues.